The Littlest Fox - Oseida, Rachel (Spectrum, 2023)
This short story was written in response to a prompt asking for reflection on how disabled individuals are affected and/or disregarded in times of crisis such as the covid-19 pandemic. The short story is also heavily influenced by primarily Russian and Ukrainian folktales, as well as general fantasy and folk myth.